From Smelter Fumes to Silk Road Winds: Exploring Legal Responses to Transboundary Air Pollution over South Korea - Laura S. Henry; Jasper Kim; Dongho Lee (Washington University Global Studies Law Review, 2012)
As China‘s industrialization has entered full swing, transboundary pollution has swept eastward across the Manchurian Plain and the Yellow Sea into neighboring Northeast Asian countries. The desertification of Mongolia and Northwestern China due to global warming has fueled seasonal yellow dust storms descending on Korea in increased frequency and intensity in recent years, acting as a vector for various kinds of air pollution. On top of sulfur dioxide and nitrous oxide that cause acid deposition which, in turn, destroys crops and forests, southeasterly winds carry fine particulate matter, aerosols, ozone, and heavy metals with more significant negative consequences on the health of humans and other species. Soaring demand for energy in China (supplied mainly by coal-fired power plants) is casting deep uncertainty on regional air quality for the future, given the historically unprecedented scale and pace of deployment of plants in such a densely populated region. It is widely assumed that coal will be China‘s principal source of energy for many decades to come, comprising as much as 70% of energy demand. According to the IEA World Energy Outlook for 2011, China will account for more than half of the global share of coal use in 2020 with conservative assumptions. However, as China rapidly becomes a major world market for internal combustion vehicles, increasing carbon monoxide emissions from vehicles are expected to contribute heavily to transboundary pollution in Asia and overtake power plants as the primary source of air pollution.
Keywords: air pollution; environmental; South Korea; transboundary